2020
DOI: 10.3389/fpubh.2020.585850
|View full text |Cite
|
Sign up to set email alerts
|

Patient Flow Dynamics in Hospital Systems During Times of COVID-19: Cox Proportional Hazard Regression Analysis

Abstract: Objectives: The present study is aimed at estimating patient flow dynamic parameters and requirement for hospital beds. Second, the effects of age and gender on parameters were evaluated.Patients and Methods: In this retrospective cohort study, 987 COVID-19 patients were enrolled from SMS Medical College, Jaipur (Rajasthan, India). The survival analysis was carried out from February 29 through May 19, 2020, for two hazards: Hazard 1 was hospital discharge, and Hazard 2 was hospital death. The starting point fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Our study found that the mortality rate from COVID-19 disease in hospitalized patients was 11.1 (95% CI 8.1–14.2). The overall COVID-19 death rate we found in this study is comparable with findings from India, 8.1% [ 18 ], New York, USA, 13.1% [ 19 ] and Mexico, 9.37% [ 20 ], while it is less than those from Belgium, 29.9% [ 21 ], and Italy, 25.2% [ 22 ]. This discrepancy between countries might be due to difficulties in conducting diagnosis tests for all suspected individuals, insufficient admission hospital capacity for less severe patients at the early stage of the pandemic and variation in the methodology for cases confirmation and death registery [ 20 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…Our study found that the mortality rate from COVID-19 disease in hospitalized patients was 11.1 (95% CI 8.1–14.2). The overall COVID-19 death rate we found in this study is comparable with findings from India, 8.1% [ 18 ], New York, USA, 13.1% [ 19 ] and Mexico, 9.37% [ 20 ], while it is less than those from Belgium, 29.9% [ 21 ], and Italy, 25.2% [ 22 ]. This discrepancy between countries might be due to difficulties in conducting diagnosis tests for all suspected individuals, insufficient admission hospital capacity for less severe patients at the early stage of the pandemic and variation in the methodology for cases confirmation and death registery [ 20 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…With respect to the simplistic modelling approach, we note that for most of the existing studies the set of predictive variables is limited to comorbidities or specific medications. For instance, [ 3 ] describes the progression of a moderate cohort of patients to death or discharge using survival methods but only age and gender as predictors. [ 5 ] and [ 6 ] consider large cohorts and combine data from different sources but they do not consider the ICU hospitalisation as an intermediate state.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, mathematical models have been used to predict the course of disease and mortality. [4][5][6][7] Such models have potential in disease management as well as preventive protocols that are cost-effective that can help optimum allocation of resources to manage the disease. [8][9][10][11][12][13][14] An econometric model has been proposed in the present study to predict and extrapolate the transmission of COVID-19.…”
Section: Data Acquisitionmentioning
confidence: 99%